2022
DOI: 10.1155/2022/7619438
|View full text |Cite|
|
Sign up to set email alerts
|

To Analyze the Influencing Factors of Senile Coronary Heart Disease Patients Complicated with Frailty Syndrome

Abstract: To analyze the influencing factors of senile coronary heart disease patients complicated with frailty syndrome. A total of 80 elderly patients with coronary heart disease admitted to our hospital from March 2020 to March 2021 were selected as the research subjects. The Fried Frailty Symptom Scale was used to evaluate whether the 80 patients were complicated with frailty syndrome. According to the evaluation results, the patients were divided into a nonfrailty syndrome group (52 cases in total) and frailty synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Its increase meant that body had continuous inflammation. In addition, the increasing levels of IL-6 were associated with some frailty features such as weight loss, bone density reduction, and thrombocytosis [26]. It was thus suggested that proactive methods to control chronic inflammation in elderly male COPD patients could reduce the frailty risk to certain extent.…”
Section: Factorsmentioning
confidence: 99%
“…Its increase meant that body had continuous inflammation. In addition, the increasing levels of IL-6 were associated with some frailty features such as weight loss, bone density reduction, and thrombocytosis [26]. It was thus suggested that proactive methods to control chronic inflammation in elderly male COPD patients could reduce the frailty risk to certain extent.…”
Section: Factorsmentioning
confidence: 99%
“…During the 6-year follow-up of the NHATS study, it was revealed that seniors with pre-frailty and frailty have higher incidences of all-cause mortality, mainly due to death, stroke and peripheral vascular disease. The means to include frailty evaluation into the care of seniors at risk for CCSs is limited due to low efficacy in the prevention of frailty, no fully efficient therapies of the frailty and limited access to comprehensive geriatric evaluation [ 46 , 47 , 48 ].…”
Section: Risk Assessment In the Frail Senior Patient With Ccsmentioning
confidence: 99%
“…Currently, tuberculosis continues to be one of the most significant infectious diseases threatening global human health. Frailty [1] refers to a syndrome in which the elderly experience a decrease in physiological reserve, thereby increasing their vulnerability. Due to this reduced capacity to withstand stress, even minor external stimuli can result in adverse outcomes such as acute illness, disability, falls, delirium, and mortality.…”
Section: Introductionmentioning
confidence: 99%